Avant-garde/Neo-avant-garde - Scheunemann, Dietrich (Avant garde critical studies ;, 2005)
"This collection of critical essays explores new approaches to the study of avant-garde literature and art, film and architecture. It offers a theoretical framework that avoids narrowly defined notions of the avant-garde. It takes into account the diversity of artistic aims and directions of the various avant-garde movements and encourages a wide and open exploration of the multifaceted and often contradictory nature of the great variety of avant-gardist innovations. Individual essays concentrate on cubist collage and dadaist photomontage, on abstract painting by members of the Dutch group De Stijl, on verbal chemistry and dadaist poetry and on body art from futurism to surrealism"--